Incidence of fistula after management of perianal abscess - Hasan, Riyadh Mohamad (Journal of Coloproctology, 2016)
Background Perianal fistula is among the most common anorectal diseases encountered in adults, men are more prone to be affected than women. There is a close relationship of abscess and fistula in etiology, anatomy, pathophysiology, therapy, complications and morbidity, it is appropriate to consider them as one entity.Aim of study To determine the incidence of fistula formation and recurrent abscess in a sample of Iraqi patients in Baghdad and decide whether primary fistulotomy should be performed at the time of incision and drainage of perianal abscesses.Patients and methods A retrospective study of 68 patients with perianal abscess operations conducted in Baghdad. They underwent incision and drainage under either local or general anesthesia at Al-Kindy Teaching Hospitals and private hospitals over a 15-year period from January 2000 to December 2015. Their ages ranged from 20 to 68 years (40.21 ± 1.34) males (63/68) (92.64%) were more than females (5/68) (7.35%). Patients were treated with incision over the abscess under anesthesia and drainage of the abscess was done. The patients were followed up for an average 18 months (range 12–24 months) after abscess drainage or until a fistula appeared and abscess recurrence.Results The study group comprised of 68 (92.64%) patients with perianal abscess with a median age 39 years (range 20–68 years). The mean follow-up period was identified to be 18 months (range 12–24 months). Males (63/68) (92.64%) were more than females (5/68) (7.35%). The incidence of fistula formation after follow up, the patients with perianal abscess after incision and drainage was 31/68 (45.58%) and males (30/31) (44.11%) were more than females (1/31) (1.47%). The most common site was posterior then left lateral position. The percentage of patients with recurrent abscess n = 6 (8.82%)were lower than fistula formation n = 31 (45.58%). The percentage of males n = 4/6 (5.88%) were more than females 2/6 (2.94%).Conclusions The incidence of anal fistula in a sample of Iraqi patients with perianal abscess was 45.58% and percentage of recurrence of perianal abscess was 8.82%. To avoid division of anal sphincter muscle, secondary fistulotomy is advised to be done later when anal fistula will be formed.
Keywords: Fistula; Perianal; Abscess